The Strategic Role of Stakeholders in Stunting Alleviation through the MACTOR Method - Diera, Miftah Ichda; Saleh, Mohammad; Yunitasari, Duwi (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This research is original because it uses a MACTOR analysis to examine the roles and interactions of stakeholders in stunting alleviation and their impact on improving the quality of human resources in Jember Regency. Research Objectives: This study aims to analyze the roles, interests, and influence of key stakeholders involved in stunting alleviation and to assess how their coordination contributes to improving human resource quality in Jember Regency. Research Methods: This research employs a mixed-methods approach, using the MACTOR method, to examine stakeholder relationships. Data were collected through interviews, document analysis, and secondary data related to stunting and human development indicators. Empirical Results: The findings indicate that stakeholder roles in stunting alleviation are uneven, with limited coordination and varying levels of influence. Weak synergy among actors reduces the effectiveness of stunting reduction programs and their impact on human resource quality. Implications: These results suggest the need for stronger stakeholder coordination, clearer role distribution, and integrated policies to enhance stunting alleviation and support sustainable human resource development in Jember Regency. JEL Classification: I15, Q01, D70, P11